Regulation of sensorimotor gating via Disc1/Huntingtin-mediated Bdnf transport in the cortico-striatal circuit - Jaaro-Peled, Hanna; Kumar, Sunil; Hughes, Dalton; Sumitomo, Akiko; Kim, Sun-Hong; Zoubovsky, Sandra; Hirota-Tsuyada, Yuki; Zala, Diana; Bruyere, Julie; Katz, Brittany M.; Huang, Beverly; Flores, Rafael; et al. (Molecular psychiatry, 2022)
Sensorimotor information processing underlies normal cognitive and behavioral traits and has classically been evaluated through prepulse inhibition (PPI) of a startle reflex. PPI is a behavioral dimension deregulated in several neurological and psychiatric disorders, yet the mechanisms underlying the cross-diagnostic nature of PPI deficits across these conditions remain to be understood. To identify circuitry mechanisms for PPI, we performed circuitry recording over the prefrontal cortex and striatum, two brain regions previously implicated in PPI, using wild-type (WT) mice compared to Disc1- locus-impairment (LI) mice, a model representing neuropsychiatric conditions. We demonstrated that the corticostriatal projection regulates neurophysiological responses during the PPI testing in WT, whereas these circuitry responses were disrupted in Disc1- LI mice. Because our biochemical analyses revealed attenuated brain-derived neurotrophic factor (Bdnf) transport along the corticostriatal circuit in Disc1- LI mice, we investigated the potential role of Bdnf in this circuitry for regulation of PPI. Virus-mediated delivery of Bdnf into the striatum rescued PPI deficits in Disc1- LI mice. Pharmacologically augmenting Bdnf transport by chronic lithium administration, partly via phosphorylation of Huntingtin (Htt) serine-421 and its integration into the motor machinery, restored striatal Bdnf levels and rescued PPI deficits in Disc1- LI mice. Furthermore, reducing the cortical Bdnf expression negated this rescuing effect of lithium, confirming the key role of Bdnf in lithium-mediated PPI rescuing. Collectively, the data suggest that striatal Bdnf supply, collaboratively regulated by Htt and Disc1 along the corticostriatal circuit, is involved in sensorimotor gating, highlighting the utility of dimensional approach in investigating pathophysiological mechanisms across neuropsychiatric disorders.